Teacher-Student Relationships at a Kindergarten School as Viewed from Classroom Management Principles - Shinta, Lucia Geneviave Bella; Febriani, Adelia; Widiati, Utami (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
Quality classroom management contributes to creating learning environment that allows the realization of various teacher roles. One way to support this is by building good teacher-student relationship. This study aims at describing the relationship between teachers and students at a kindergarten school in Malang and discusses its aspects in relation to classroom management principles. After conducting qualitative research using one-week classroom observation and literature study, this study found that almost all aspects of teacher-student relationship were identified, namely conducting informal conversations with students, paying attention to students’ activities, using physical gestures and movements, implementing positive interaction strategies, providing affirmative reactions to incorrect responses, and exhibiting an assertive connection. The other aspect that was missed was acknowledging students’ different characteristics